Erythrocyte-mimicking paclitaxel nanoparticles for improving biodistributions of hydrophobic drugs to enhance antitumor efficacy - Zheng Zhai; Pengcheng Xu; Jun Yao; Ridong Li; Lidong Gong; Yuxin Yin; Zhiqiang Lin (Taylor & Francis Group, 2020)
Recent decades have witnessed several nanocrystal-based hydrophobic drug formulations because of their excellent performance in improving drug loading and controlling drug release as mediate drug forms in tablets or capsules. However, the intravenous administration of drug nanocrystals was usually hampered by their hydrophobic surface properties, causing short half-life time in circulation and low drug distribution in tumor. Here, we proposed to enclose nanocrystals (NC) of hydrophobic drug, such as paclitaxel (PTX) into erythrocyte membrane (EM). By a series of formulation optimizations, spherical PTX nanoparticles (PN) with the particle size of around 280 nm were successfully cloaked in erythrocyte membrane, resulting in a PTX-NP-EM (PNM) system. The PNM could achieve high drug loading of PTX (>60%) and stabilize the particle size significantly compared to PN alone. Besides, the fluorescence-labeling PNM presented better tumor cell uptake, stronger cytotoxicity, and higher drug accumulation in tumor compared to PN. Finally, the PNM was found to be the most effective against tumor growth among all PTX formulations in tumor-bearing mice models, with much lower system toxicity than control formulation. In general, the PNM system with high drug-loading as well as superior bio-distributions in vivo could be served as a promising formulation.